Revised Seventh Five Year Plan 1985-90 Vol. IV Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1986)
It is an established fact that statistics play a vital role in the formulation and execution of development plans. Since the inception of Planning in this country notable efforts have been made to identify the gas in the statistical data to specify the steps required to fill the gaps. Organizations such as central statistical organization and Labour Bureau have played a vital role in this connection. As a sequel to this the statistical Machinery of this Union Territory has to be strengthened and Statistical cells to be created. Till date the entire statistical work of this Union Territory is attended by one statistical assistant in the Secretariat. There is no technical Officer to guide the Statistical Assistant properly for the preparation of basic and reliable statistics for policy making. Further there are no field staffs available for collection of various statistics required for formulating schemes and plans except two Junior Investigators.
Union Territory of Lakshadweep
Planning Department Secretariat, Lakshadweep Kavaratti
Keywords: Secretariat Economic Services; Tourism; Weights and Measures; General Education; Art and Culture; Sports and Youth Services; Medical and Public Health; Water Supply and Sanitation; Housing including police housing; Strengthening of District Administration.